Traditional concepts of space in contemporary Chinese family compounds - Hung, Inah Francesca T. (College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT The purpose of this study was to discover if contemporary family compounds of the Chines were still influenced by traditional concepts of space centered on social, cultural, and religious values. This study was descriptive in nature and employed qualitative data collected through documentation, observation, and interview. Purpose sampling was utilized to select five (5) compounds in Metro Manila where five (5) extended Chinese families lived. The instruments of the study included documentation forms, observation schedule, and interview schedule. One representative from each family was chosen for the interview. The Chinese traditional values that still manifested in the family compounds were priority for male children, deference for seniority, belief in the cult of ancestors, close relations with the family, and ceremonial hospitality. Sons were each given a house in the compound while household heads and elders of the family were given the best and biggest spaces. It was also evident that the family provided structures and spaces for the worship of ancestors, access to the main doors of each house, and gathering areas to receive family and guests during gatherings. Values that were no longer reflected in the space included discrimination against women in the family, separation of sexes at social gatherings, and hierarchy between brothers. Results also revealed that the reasons for maintaining these traditional values and concepts of space were greatly influenced by the elders and household heads and the importance they gave to their family's history. Other factors like the actual needs of the families and practicality also appeared to have affected the space planning of these residences.